General Description of Sa'diddin Hamavi's Works - Rajabov Alisher Shavkatovich (Researchparks Publishing, 2026)
A distinctive feature of Hamavi's work is that it goes beyond traditional practical mysticism and deals with theoretical knowledge and the philosophy of being.